Src is required for mechanical stretch-induced cardiomyocyte hypertrophy through angiotensin II type 1 receptor-dependent β-arrestin2 pathways. - Shijun Wang (Public Library of Science (PLoS), 2014)
Angiotensin II (AngII) type 1 receptor (AT1-R) can be activated by mechanical stress (MS) without the involvement of AngII during the development of cardiomyocyte hypertrophy, in which G protein-independent pathways are critically involved. Although β-arrestin2-biased signaling has been speculated, little is known about how AT1-R/β-arrestin2 leads to ERK1/2 activation. Here, we present a novel mechanism by which Src kinase mediates AT1-R/β-arrestin2-dependent ERK1/2 phosphorylation in response to MS. Differing from stimulation by AngII, MS-triggered ERK1/2 phosphorylation is neither suppressed by overexpression of RGS4 (the negative regulator of the G-protein coupling signal) nor by inhibition of Gαq downstream protein kinase C (PKC) with GF109203X. The release of inositol 1,4,5-triphosphate (IP3) is increased by AngII but not by MS. These results collectively suggest that MS-induced ERK1/2 activation through AT1-R might be independent of G-protein coupling. Moreover, either knockdown of β-arrestin2 or overexpression of a dominant negative mutant of β-arrestin2 prevents MS-induced activation of ERK1/2. We further identifies a relationship between Src, a non-receptor tyrosine kinase and β-arrestin2 using analyses of co-immunoprecipitation and immunofluorescence after MS stimulation. Furthermore, MS-, but not AngII-induced ERK1/2 phosphorylation is attenuated by Src inhibition, which also significantly improves pressure overload-induced cardiac hypertrophy and dysfunction in mice lacking AngII. Finally, MS-induced Src activation and hypertrophic response are abolished by candesartan but not by valsartan whereas AngII-induced responses can be abrogated by both blockers. Our results suggest that Src plays a critical role in MS-induced cardiomyocyte hypertrophy through β-arrestin2-associated angiotensin II type 1 receptor signaling.